Korean-English language translational action of K-Pop social media content: a case study on Bangtan Sonyeondan’s (BTS) official twitter - Aznur Aisyah, (Penerbit Universiti Kebangsaan Malaysia, 2017)
K-pop fans face language barriers on a daily basis when searching for their favourite K-Pop group related news. The translators’ role in mediating information between the international fans with the K-Pop artists is central in delivering the necessary information to its fans around the globe. This study has been motivated by the scarcity of research on the progress of translation in social media microblogging such as Twitter. It was aimed at analysing translation progress occurring in social media, namely the Twitter account, where communication discourse activities actively occurred. Big Hit Entertainment’s Twitter account (@BigHitEnt) was selected as the primary data sample because of the outstanding reputation of Bangtan Sonyeondan (BTS), a K-Pop idol group under the company’s label, in terms of social media engagement. This research employed the Social Media Translational Action (SoMTA) analytical framework, a new research methodology adapted from the Translational Action framework, for its data analysis. . The content of the news feed in Twitter’s timeline is mostly written in the Korean language which might not be understood by the international fans who do not speak Korean. Thus, this research investigated the translation progress when @BigHitEnt created new timelines on their account, particularly those related to their promotion of new albums beginning with the “Love Yourself” series. It is hoped that this research would provide fresh insights into the current state of the translation world within this cyber age era using the new translation analysis.